2018
DOI: 10.1155/2018/8572571
|View full text |Cite
|
Sign up to set email alerts
|

3,5‐Dicaffeoyl‐Epi‐Quinic Acid Isolated from Edible Halophyte Atriplex gmelinii Inhibits Adipogenesis via AMPK/MAPK Pathway in 3T3‐L1 Adipocytes

Abstract: Atriplex gmelinii is an edible halophyte that has been suggested to possess various health benefits. In the present study, 3,5-dicaffeoyl-epi-quinic acid (DEQA) isolated from A. gmelinii was tested for its ability to prevent adipogenesis in 3T3-L1 cells. Also, the molecular mechanisms by which DEQA affects differentiation of 3T3-L1 cells were investigated. The introduction of DEQA to differentiating 3T3-L1 preadipocytes resulted in suppressed adipogenesis and lowered expression of adipogenesis-related factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…On the other hand, luteolin-OSO 3 Na treatment slightly increased AMPK phosphorylation, however not comparable to luteolin. These results were parallel to MAPK activation as reports had shown that activation of p38, ERK, and JNK MAPKs during adipogenesis was in the opposite manner with AMPK activation [ 15 , 23 ]. Effect of samples on MAPK activation was further analyzed by flow cytometry assessing the expression of phosphorylated MAPK (ERK1/2) in adipo-induced hBM-MSCs.…”
Section: Resultssupporting
confidence: 74%
“…On the other hand, luteolin-OSO 3 Na treatment slightly increased AMPK phosphorylation, however not comparable to luteolin. These results were parallel to MAPK activation as reports had shown that activation of p38, ERK, and JNK MAPKs during adipogenesis was in the opposite manner with AMPK activation [ 15 , 23 ]. Effect of samples on MAPK activation was further analyzed by flow cytometry assessing the expression of phosphorylated MAPK (ERK1/2) in adipo-induced hBM-MSCs.…”
Section: Resultssupporting
confidence: 74%
“…3,5-Dicaffeoyl-epi-quinic acid (DCEQA) was isolated from Atriplex gmelinii as a white powder. Isolation, characterization, and identification of the compound were carried out as reported earlier [21].…”
Section: Isolation Of 35-dicaffeoyl-epi-quinic Acidmentioning
confidence: 99%
“…e remaining cycles consisted of 42°C for 60 min and 72°C for 5 min. e target cDNA was amplified using the sense and antisense primers as previously noted [21]. e amplification was carried out with 30 cycles; each cycle consisted of 95°C for 45 sec, 60°C for 1 min, and 72°C for 45 sec.…”
Section: Reverse Transcription Semiquantitative Polymerase Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeoylquinic acid and its derivatives have been reported to show antioxidant [ 17 ], antibacterial [ 18 ], antiviral [ 19 ] and antiobesic effects [ 20 ]. Previous studies have demonstrated the protective effect of 3,5-dicafeoyl-epi-qinic acid (DEQA) in UVB-irradiated keratinocytes [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%